The Struggle for Independence in Guinea-Bissau - Carlos Eduardo Sangreman; Rui Jorge Semedo (Advanced Studies on Socio-Economy Development, 2022)
The realization of the process of armed struggle for national liberation in the so called Portuguese Guinea and, consequent unilateral proclamation of the State of Guinea-Bissau in September 1973 was possible from outside the Guinean borders, through an important and strategic contribution made by the Republic of Guinea- Conakry which in 1958 had already achieved national independence. This article intends to observe the capital of the neighboring Republic of Guinea as a symbolic structuring space in the construction of ideological antagonisms based on the sociocultural and political dispute around